Grammatical Errors Writing Challenges in Creative Writing Course by English Literature Sophomore Students in an Indonesian University - Tarru Mata, Yegar; Yulianto, Andrias (Fakultas Ilmu Budaya, Universitas Brawijaya, 2025)
This study explores the grammatical errors frequently found in the creative writing of sophomore English Literature students and the underlying challenges contributing to these errors. Through the analysis of student writing tests, member checking, interviews, and inter-rater validation, the study determines that misformation is the most common error type, followed by omission, misordering, and addition. The findings show that many students lack metalinguistic awareness and are often unaware of their errors. Factors contributing to this include first language interference, lack of grammatical knowledge, overgeneralization, stress, low confidence, and lack of feedback. These findings suggest a gap between students' communicative fluency and grammatical accuracy. The study finds that combining grammar instruction with writing practice, as well as reflective and feedback-based strategies, can help students improve their writing performance in EFL contexts.